Association of Dementia Severity and Caregiver Support With Early Discharge From Home Health. (3rd October 2022) - Knox, Sara; Haas, Allen; Downer, Brian; Ottenbacher, Kenneth J.
Introduction: The objective of this study was to examine the relationship between dementia severity and early discharge from home health. Methods: This was a retrospective study of 100% national Medicare home health da ta files (2016-2017). Multilevel logistic regression was used to study the relationship of dementia severity, caregiver support, and medication assistance with early discharge from home health. Results: The final cohort consisted of 91 302 Medicare beneficiaries with an ADRD diagnosis. A pattern of early discharge rates across dementia severity levels was not demonstrated. The relative risk for early discharge was lower for individuals who needed assistance with medication and for those with unmet caregiver needs. Discussion: The findings of this study do not support the hypothesis that dementia severity contributes to early discharge from home health. Further research is needed to fully understand key factors contributing to early discharge from home health.